2019
DOI: 10.1089/rej.2017.2048
|View full text |Cite
|
Sign up to set email alerts
|

Frailty and Rejuvenation with Stem Cells: Therapeutic Opportunities and Clinical Challenges

Abstract: Frailty, one appealing target for improving successful aging of the elderly population, is a common clinical syndrome based on the accumulation of multisystemic function declines and the increase in susceptibility to stressors during biological aging. The age-dependent senescence, the frailty-related stem cell depletion, chronic inflammation, imbalance of immune homeostasis, and the reduction of multipotent stem cells collectively suggest the rational hypothesis that it is possible to (partially) cure frailty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 108 publications
(154 reference statements)
0
21
0
Order By: Relevance
“…Auto-transplantation of MSCs has been shown to improve the function of MSCs extracted from patients (Sun, 2019). The same is urgently needed to improve MSC performance in vitro.…”
Section: Rejuvenation Of Senescent Mscsmentioning
confidence: 99%
“…Auto-transplantation of MSCs has been shown to improve the function of MSCs extracted from patients (Sun, 2019). The same is urgently needed to improve MSC performance in vitro.…”
Section: Rejuvenation Of Senescent Mscsmentioning
confidence: 99%
“…With the process of aging, frailty may be caused by multiple causes and contributors, including genetic and environmental factors 21 - 24 . To be more specific, genome instability 25 , DNA damage 26 , epigenetic alternations 27 , loss of proteostasis 28 , oxidative stress 29 , chronic inflammation 30 , mitochondrial dysregulation 31 , and stem cell exhaustion 24 , 32 are involved in the progression of aging frailty. These hallmarks are interconnected and ultimately lead to cellular senescence.…”
Section: Overview Of Aging Frailty and Its Pathophysiologymentioning
confidence: 99%
“…Recently, randomized double blind studies showed that intravenous administration of allogeneic MSCs is safe, renders improved physical performance, and reduces inflammatory markers increased in frailty states. [42][43][44][45] In the first of these trails, 15 patients with mild to moderate frailty were treated with MSCs.…”
Section: Clinical Trials Using Mscs Against Frailtymentioning
confidence: 99%